Effects of cycling on the morphology and spinal posture in professional and recreational cyclists: a systematic review - Antequera-Vique, A. J.; Oliva-Lozano, J. M.; Muyor, J. M. (Sports Biomechanics, 2023)
The aim was to know if cycling affects spinal morphology in postures off the bicycle, such as adapting the spinal curvatures on the bicycle depending on the handlebar type and position on the handlebars. A systematic review was conducted following the PRISMA guidelines. The studies selected met the following criteria: a) the study design was cross-sectional or longitudinal (experimental or cohorts); b) the study evaluated the sagittal morphology of the spine on the bicycle; c) the study included healthy and trained participants without injuries or cyclists reporting low back pain. Fifteen studies reported that a greater pelvic tilt was observed that when the handlebar was in a lower position. Sixteen studies found that lumbar kyphosis was greater when the handlebar grip was lower and farther from the saddle. Twelve studies reported that a tendency towards greater thoracic flexion as the time spent pedalling on the bicycle increased. In conclusion, the practice of cycling produces adaptations in the morphology of the spine of the cyclist compared to non-cyclists, such as an increase in pelvic tilt and a greater capacity for lumbar flexion in trunk flexion positions, and a greater thoracic kyphosis in the standing position.